Comentarios a la Constitución Española de 1978 / dirigidos por Oscar Alzaga Villaamil. T.IX. Artículos 113 a 127 / Francisco Fernández Segado...[et al.] - Alzaga Villaamil, ÓscarFernández Segado, Francisco
Referencias bibliográficas